2013
DOI: 10.1002/jgrb.50154
|View full text |Cite
|
Sign up to set email alerts
|

A decade of horizontal deformation from great earthquakes

Abstract: The 21st Century has seen the occurrence of 17 great earthquakes (Mw >8), including some of the largest earthquakes ever recorded. Numerical modeling of the earthquakes shows that nearly half of the Earth's surface has undergone horizontal coseismic deformation >1 mm, with the 2004 Sumatra‐Andaman earthquake dominating the global deformation field. This has important implications for both the realization of a terrestrial reference frame and in the interpretation of regional tectonic studies based on GPS veloci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 51 publications
(89 reference statements)
4
52
0
Order By: Relevance
“…A strong EQ have an effect on the time series analysis causing some discontinuities as offsets, which may lead to an unrealistic estimation of geodetic velocities (Bitharis et al, 2015). More generally (Tregoning et al, 2013) showed that large EQs can induce linear velocity errors of up to 0.4 mm/yr at sites over 1000 km from the earthquake locations. In Figure 2, daily displacements expressed in the topocentric (North, East, Up) system are presented for 018B (Samothrace Island) and LEMN (Lemnos Island) stations, which are the two nearest to the EQ epicentre.…”
Section: Time Series Daily Displacementsmentioning
confidence: 99%
“…A strong EQ have an effect on the time series analysis causing some discontinuities as offsets, which may lead to an unrealistic estimation of geodetic velocities (Bitharis et al, 2015). More generally (Tregoning et al, 2013) showed that large EQs can induce linear velocity errors of up to 0.4 mm/yr at sites over 1000 km from the earthquake locations. In Figure 2, daily displacements expressed in the topocentric (North, East, Up) system are presented for 018B (Samothrace Island) and LEMN (Lemnos Island) stations, which are the two nearest to the EQ epicentre.…”
Section: Time Series Daily Displacementsmentioning
confidence: 99%
“…SAMP) as this work focuses only on stations in the far-field of an event. Following the studies of Watson et al (2010) and Tregoning et al (2013), we also discard the GPS stations which were strongly offset by the Macquarie Ridge earthquake (2004 December 23) which had a magnitude equal to M w 8 (e.g. AUCK, DUNT,CHAT,MAC1,HOB2,TIDB and MOBS).…”
Section: Gps Processing and Methodologymentioning
confidence: 99%
“…The parameters to model the SumatraAndaman earthquake are exactly the same as the values of Pollitz et al (2006). The estimated values are the same as in Tregoning et al (2013) and displayed in Appendix C.…”
Section: Gps Processing and Methodologymentioning
confidence: 99%
See 2 more Smart Citations